DisArt: Redefining the Construct of Participation - Jennifer Fortuna (Scholarworks @ WMU, 2018)
DisArt, an arts and culture organization based in Grand Rapids, MI, provided the cover art for the Spring 2018 issue of the Open Journal of Occupational Therapy (OJOT). The piece, a somatic sculpture by Petra Kuppers, was featured at the 2015 DisArt Festival in Grand Rapids. Kuppers is a disability culture activist and community performance artist who connects people, both disabled and nondisabled, in public spaces. DisArt's mission is to increase the participation of disabled people in our communities through disability art exhibitions, cutting edge public events, and consultation. In a recent interview, DisArt co-founders and executive directors, Dr. Christopher Smit, PhD, and Jill Vyn, MSW, share how DisArt is redefining the construct of participation for people with and without disabilities.